PFAS Research in Nigeria: Where Are We? - Abdullahi Tunde Aborode; Peter Olusakin Oladoye; Seto Charles Ogunleye; Raymond Femi Awoyemi; Abayomi Oyeyemi Ajagbe; Samuel Babatunde Ajibade; Ridwan Olamilekan Adesola (SAGE Publishing, 2024)
The persistence of per- and polyfluoroalkyl substances (PFAS) in the environment and their possible negative health impacts have attracted global attention. In Nigeria, there have been instances of PFAS contamination in many environmental areas, such as water sources. This paper raised concerns regarding limited research of PFAS in Nigeria, potential human exposure, and environmental consequences in Nigeria. This paper examines the present status of PFAS research in Nigeria, the sources from which contamination occurs, the environmental effects, and the implications for human health. This underscores the holes in understanding and areas of focus for study, underscoring the necessity for thorough evaluations of potential risks and regulatory actions to reduce exposure to PFAS and protect public health and the environment in Nigeria.